Membrane biofouling and scaling in forward osmosis membrane bioreactor - Zhang, Jinsong (2013)
The forward osmosis membrane bioreactor (FOMBR) has received much attention recently. Due to the high rejection nature of FO membranes, the biomass, dissolved organic and inorganic compounds retained in the bioreactor could cause membrane fouling by multiple mechanisms. In this study, a 45% permeate flux decrease was observed in a well controlled FOMBR equipped with a submerged hollow fiber FO membrane module with the active layer facing the draw solution (AL-DS) configuration. A series of characterizations were performed to explore membrane fouling mechanisms in the FOMBR. It was found that a biofouling layer covered the substrate surface of the FO membrane with a combined structure of bacterial clusters and extracellular polymeric substances (EPS), which contributed to 72% drop of the membrane mass transfer coefficient (Km) and around 10% increase in the hydraulic resistance. The inorganic fouling was caused by Ca, Mg, Al, Si, Fe and P that contributed 60% of the total hydraulic resistance of the fouled membrane and decreased the Km by around 34%. These results suggest that in this application the FO fouling is governed by the coupled influences of biofilm formation and inorganic scaling. When the configuration was reversed with the active layer facing the feed solution (AL-FS), a negligible flux decline was obtained by applying intermittent tap water flushing to the membrane surface, which suggests that the AL-FS orientation is favorable for FOMBR operation. An effective strategy for fouling control is to prevent internal scaling and the over-growth of biofilm on the membrane surface.